The Role of Islamic Student Groups in the Reformasi Struggle: KAMMI (Kesatuan Aksi Mahasiswa Muslim Indonesia) - Richard G. Kraince (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
This article provides an investigation of KAMMI's role in the reformasi movement with respect to its relationship with the nation, the umat, and the larger student movement. As it explores the pressures that have confronted Islamic students throughout the period, it addresses some of the most salient topics currently being debated in Indonesian society. Most importantly, it provides an analysis of KAMMI's stance toward the legitimacy of former president B. J. Habibie's government and its right to lead reform as opposed to the positions of several